Multimodal Analysis of Topic Shift in Persian Dyadic Conversations (JOURNAL OF ADVANCES IN LINGUISTICS, 2015)
Conversations play an important role in our daily life. During conversations, we usually talk from topic to topic automatically, smoothly and effortlessly. However, there are sometimes difficulties experienced in establishing and also acknowledging a new topic in an ongoing conversation. This fact shows that there are specific features and mechanisms to both producing and perceiving topic change, which play a prominent role in keeping continuous talk. The present study provides a multimodal analysis of the occurrence of topic shift in dyadic conversations which were recorded both for audio and video. The research was carried out on two stages, studying both visual and prosodic features of topic shift. On the first stage, the actual speakers gaze movements around topic shift were investigated while on the second stage, prosodic features such as pitch movement and intensity surrounding topic shift were measured. We wanted to know whether any of these features and their combination could be used as a cue to detect topic shift in a conversation. Focusing on detection and analysis of these features could be helpful for a better understanding of human-human as well as human-machine communication.